The proximate unit in Chinese handwritten character production - Chen, Jenn-Yeu; Cherng, Rong-Ju (Frontiers in Psychology, 2013)
In spoken word production, a proximate unit is the first phonological unit at the sublexical level that is selectable for production (O’Seaghdha, Chen, & Chen, 2010). The present study investigated whether the proximate unit in Chinese handwritten word production is the stroke, the radical, or something in between. A written version of the form preparation task was adopted. Chinese participants learned sets of two-character words, later were cued with the first character of each word, and had to write down the second character (the target). Response times were measured from the onset of a cue character to the onset of a written response. In Experiment 1, the target characters within a block shared (homogeneous) or did not share (heterogeneous) the first stroke. In Experiment 2, the first two strokes were shared in the homogeneous blocks. Response times in the homogeneous blocks and in the heterogeneous blocks were comparable in both experiments (Exp. 1: 687 ms vs. 684 ms, Exp. 2: 717 vs. 716). In Experiment 3 and 4, the target characters within a block shared or did not share the first radical. Response times in the homogeneous blocks were significantly faster than those in the heterogeneous blocks (Exp. 3: 685 vs. 704, Exp. 4: 594 vs. 650). In Experiment 5 and 6, the shared component was a Gestalt-like form that is more than a stroke, constitutes a portion of the target character, can be a stand-alone character itself, can be a radical of another character but is not a radical of the target character (e.g., 士in聲, 鼓, 穀, 款; called a logographeme). Response times in the homogeneous blocks were significantly faster than those in the heterogeneous blocks (Exp. 5: 576 vs. 625, Exp. 6: 586 vs. 620). These results suggest a model of Chinese handwritten character production in which the stroke is not a functional unit, the radical plays the role of a morpheme, and the logographeme is the proximate unit.